Antimicrobial, antitrypanosomal and antibiofilm activity of Equisetum hyemale. (December 2016) - dos Santos Alves, Camilla Filippi; Bonez, Pauline Cordenonsi; de Souza, Marcia de Ebling; da Cruz, Ritiel Corrêa; Boligon, Aline Augusti; Piana, Mariana; Brum, Thiele Facim; Rossi, Grazielle Guidolin; Jesus, Roberta da Silva; Grando, Thirssa Helena; Monteiro, Silvia Gonzalez; Anraku de Campos, Marli Matiko; et al.
Abstract: This study evaluates, for the first time, the antibiofilm, antimicrobial and antiparasitic potential of crude extract and fractions of stems of Equisetum hyemale against several infectious agents (bacteria, fungi, Mycobacterium and Trypanosomes ) by broth microdilution technique and investigates the phenolic composition of the plant by high performance liquid chromatography. The crude extract and fractions showed antimicrobial activity, as they were capable of inhibiting the growth of bacteria in minimal inhibitory concentrations (MICs) ranging from 52.4 mg/mL to 3.27 mg/mL. For Candida species, the MICs ranged from 52.4 mg/mL to 6.5 mg/mL, and for Mycobacterium species from 2.5 mg/mL to 0.625 mg/mL. The dichloromethane fraction was able to reduce 83% of Pseudomonas aeruginosa biofilm formation and 51% of Candida albicans biofilms. The n-butanol fraction presents an important protozoal effect, reducing 100% of Trypanosoma evansi trypomastigotes after 9 h of exposure. The HPLC analysis revealed that the major substances are rosmarinic acid in dichloromethane fraction (7.38 ± 0.08 mg/g FS) and chlorogenic acid in ethyl acetate fraction (8.4 ± 0.26 mg/g FS). The crude extract and fractions of E. hyemale can be both useful and effective agents as a sustainable alternative for the treatment and prevention of several infectious agents. Highlights: Equisetum hyemale presents: important antimicrobial activity (against bacteria, fungi, Mycobacterium and Trypanosomes ). Equisetum hyemale was able to reduce biofilms. The HPLC analysis revealed rosmarinic and chlorogenic acid.